SCD1 Confers Temozolomide Resistance to Human Glioma Cells via the Akt/GSK3β/β-Catenin Signaling Axis - Dai, Shuang; Yan, Yuanliang; Xu, Zhijie; Zeng, Shuangshuang; Qian, Long; Huo, Lei; Li, Xuejun; Sun, Lunquan; Gong, Zhicheng (Frontiers in Pharmacology, 2018)
Resistance to temozolomide (TMZ), the standard chemotherapy agent for glioblastoma (GBM), poses a major clinical challenge to GBM prognosis. Understanding the mechanisms of TMZ resistance can help to identify novel drug targets and more effective therapies. Recent studies suggest that bioenergetic alterations of cancer cells play important roles in drug resistance. In our study, the altered metabolism of cancer cells was observed using a metabolic PCR array. We found that stearoyl-coenzyme A desaturase 1 (SCD1), a key rate-limiting enzyme for synthesis of monounsaturated fatty acids, was significantly upregulated in TMZ-resistant GBM cells compared to their parental counterparts. Overexpression of SCD1 promoted resistance to TMZ in parental GBM cells, whereas SCD1 depletion by siRNA could re-sensitize TMZ-resistant cells in vitro. Combinational treatment of TMZ and an SCD1-specific inhibitor showed a combined inhibitory effect on TMZ-resistant glioma cells. We also observed that overexpression of SCD1 promoted Akt/GSK3β/β-catenin signaling, while silencing of SCD1 inhibited the signaling. The combination of an Akt activator with exogenous SCD1 or the combined inhibition of Akt and enforced expression of SCD1 resulted in the most significant changes of Akt signaling. Functionally, significantly lower viability and mobility rates were observed in TMZ-resistant cells when treated with Akt inhibitors and an SCD1 inhibitor simultaneously compared to when treated individually. In conclusion, our study identified SCD1 along with its functional pathway as a novel target in the development of TMZ resistance. SCD1 inhibition used alone or in combination with Akt inhibition could effectively overcome TMZ resistance in gliomas.